The gut dysbiosis of mothers with gestational diabetes and its correlation with diet - Roya Sohrabi; Seyedeh Neda Mousavi; Reza Shapouri; Zahra Nasiri; Siamak Heidarzadeh; Rasoul Shokri (Scientific Reports)
Abstract The gut dysbiosis has been observed in gestational diabetes mellitus (GDM). However, changes in bacterial population are different among various countries due to genetic, environmental, and dietary differences. We compared the gut dominant phylum and some genus in GDM versus normo-glycemic pregnant in Iranian population, considering dietary intake. In this case-control study, 50 women diagnosed with GDM and 50 healthy pregnant, aged 18–35 yrs, during spring and summer, were participated. GDM was diagnosed based on the International Association of Diabetes and Pregnancy Groups criteria. The bacterial populations were determined based on 16SrRNA gene expression. Actinomycetota (p = 0.02), and Bifidobacterium spp. (p = 0.001) was significantly higher in the gut of healthy mothers than the GDM. However, bacteroides was significantly higher in the gut of GDM mothers than the healthies (p = 0.02). Daily calorie intake showed a negative correlation with population of Bacteroidota (p = 0.04) and Actinomycetota (p = 0.009), but dietary carbohydrate and fat showed a positive correlation. Increase in dietary intake of mono- and poly-unsaturated fatty acids (MUFAs and PUFAs) was associated with higher Bacteroidota in the gut (p = 0.02 and p = 0.04). However, dietary cholesterol showed a negative correlation with population of Bacteroidota and Bifidobacterium spp. (p = 0.003 and p = 0.02). GDM was correlated with the gut dysbiosis. Daily calorie and cholesterol intake was positively associated with dysbiosis. However total intake of carbohydrates, MUFAs and PUFAs showed a protective effect.